2018
DOI: 10.1186/s13071-018-2865-x
|View full text |Cite
|
Sign up to set email alerts
|

Larval density mediates knockdown resistance to pyrethroid insecticides in adult Aedes aegypti

Abstract: BackgroundUnderstanding mechanisms driving insecticide resistance in vector populations remains a public health priority. To date, most research has focused on the genetic mechanisms underpinning resistance, yet it is unclear what role environmental drivers may play in shaping phenotypic expression. One of the key environmental drivers of Aedes aegypti mosquito population dynamics is resource-driven intraspecific competition at the larval stage. We experimentally investigated the role of density-dependent larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…aegypti may be explained through multiple kdr mutations as well as other potential mechanisms of resistance 32 . Previous studies 27 , 33 and analyses of a random sample of 100 adult female Ae . aegypti from this study (50 survivors and 50 dead from the space spraying trial) showed that another kdr mutation (C1534) was found in ~100% of all tested mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti may be explained through multiple kdr mutations as well as other potential mechanisms of resistance 32 . Previous studies 27 , 33 and analyses of a random sample of 100 adult female Ae . aegypti from this study (50 survivors and 50 dead from the space spraying trial) showed that another kdr mutation (C1534) was found in ~100% of all tested mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as this study did not explicitly quantify selection, future studies should focus on the evolutionary consequences of repeated insecticide applications over multiple generations and on various pyrethroid resistance mechanisms, both in the field and the lab. Recent evidence shows that environmental conditions (e.g., larval habitats 33 ) or individual level variation (e.g., attributes of the gut microbiota 39 ) can greatly affect mosquito resistant phenotypes. Consequently, assessing the evolutionary implications of household insecticide use will require a comprehensive study integrating laboratory and field experimentation.…”
Section: Discussionmentioning
confidence: 99%
“…Each pan received approximately 4 pellets and the water was changed every 3 days. This regimen ensured that larvae were not crowded, as high larval densities can suppress insecticide resistance [45]. When pupae started to appear, they were removed daily and placed into small cups with water within BugDorm-1 Insect Rearing Cages (Bugdorm Store, Mega View Science, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
“…Increased food availability during the aquatic immature stages of various mosquito species is known to increase insecticide resistance ( Grossman et al, 2018 ; Ong and Jaal, 2018 ; Owusu et al, 2017 ). Strikingly, the effect of high larval densities (which translates to fiercer competition for nutrients) can revert the resistance phenotype in genetically resistant larvae ( Grossman et al, 2018 ). Similar effects are found in adult female mosquitoes, where blood-fed females are generally more resistant than unfed females ( Machani et al, 2019 ).…”
Section: From Controlled Bioassays To Field Reality: Spatio-temporal Variation In Resistancementioning
confidence: 99%